Enhanced Bacterial Wilt Resistance in Potato Through Expression of Arabidopsis EFR and Introgression of Quantitative Resistance from Solanum commersonii - Boschi, Federico; Schvartzman, Claudia; Murchio, Sara; Ferreira, Virginia; Siri, Maria I.; Galván, Guillermo A.; Smoker, Matthew; Stransfeld, Lena; Zipfel, Cyril; Vilaró, Francisco L.; Dalla-Rizza, Marco (Frontiers in Plant Science, 2017)
Bacterial Wilt caused by Ralstonia solanacearum is responsible for substantial losses in cultivated potato (Solanum tuberosum) crops worldwide. Resistance genes have been identified in wild species; however, introduction of these through classical breeding has achieved only partial resistance, which has been linked to poor agronomic performance. The Arabidopsis thaliana (At) pattern recognition receptor EF-TU RECEPTOR (EFR) recognizes the bacterial pathogen-associated molecular pattern elongation factor Tu (EF-Tu) (and its derived peptide elf18) to confer anti-bacterial immunity. Previous work has shown that transfer of AtEFR into tomato confers increased resistance to R. solanacearum. Here, we evaluated whether the transgenic expression of AtEFR would similarly increase bacterial wilt resistance in a commercial potato line (INIA Iporá), as well as in a breeding potato line (09509.6) in which quantitative resistance has been introgressed from the wild potato relative Solanum commersonii. Resistance to R. solanacearum was evaluated by damaged root inoculation under controlled conditions. Both INIA Iporá and 09509.6 potato lines expressing AtEFR showed greater resistance to R. solanacearum, with no detectable bacteria in tubers evaluated by multiplex-PCR and plate counting. Notably, AtEFR expression and the introgression of quantitative resistance from S. commersonii had a significant additive effect in 09509.6-AtEFR lines. These results show that the combination of heterologous expression of AtEFR with quantitative resistance introgressed from wild relatives is a promising strategy to develop bacterial wilt resistance in potato.